A traumatic tale of two cities: a comparison of outcomes for adults with major trauma who present to differing trauma centres in neighbouring Canadian provinces. Issue 2 (13th July 2017) - Hayre, Jefferson; Rouse, Colin; French, James; Fraser, Jacqueline; Watson, Ian; Benjamin, Sue; Chisholm, Allison; Stoica, George; Sealy, Beth; Erdogan, Mete; Green, Robert; Atkinson, Paul
ABSTRACT: Objectives: While the use of formal trauma teams is widely promoted, the literature is not clear that this structure provides improved outcomes over emergency physician delivered trauma care. The goal of this investigation was to examine if a trauma team model with a formalized, specialty-based trauma team, with specific activation criteria and staff composition, performs differently than an emergency physician delivered model. Our primary outcome was survival to discharge or 30 days. Methods: An observational registry-based study using aggregate data from both the New Brunswick and Nova Scotia trauma registries was performed with data from April 1, 2011 to March 31, 2013. Inclusion criteria included patients 16 years-old and older who had an Injury Severity Score greater than 12, who suffered a kinetic injury and arrived with signs of life to a level-1 trauma centre. Results: 266 patients from the trauma team model and 111 from the emergency physician model were compared. No difference was found in the primary outcome of proportion of survival to discharge or 30 days between the two systems (0.88, n=266 vs. 0.89, n=111; p=0.8608). Conclusions: We were unable to detect any difference in survival between a trauma team and an emergency physician delivered model. RÉSUMÉ: Objectifs: Bien que la formation d'équipes structurées, spécialisées en traumatologie soit grandement préconisée, il n'est pas clair dans la documentation que ce genre de structure donne de meilleurs résultats que ceux produits par les urgentologues chargés de la prestation des soins d'urgence. L'étude avait donc pour but d'examiner si le modèle des équipes structurées en traumatologie, dotées d'un personnel particulier, divisées en spécialités et mobilisées selon certains critères avait un rendement différent du modèle des urgentologues responsables de la prise en charge. Le principal critère d'évaluation consistait en la survie au moment du congé ou au bout de 30 jours. Méthode: Il s'agit d'une étude d'observation, fondée sur des données agrégées, provenant des registres de traumatismes du Nouveau-Brunswick et de la Nouvelle-Écosse et recueillies du 1 er avril 2011 au 31 mars 2013. Les critères de sélection comprenaient des patients âgés de 16 ans et plus, qui avaient un indice de gravité des blessures supérieur à 12, qui avaient subi des lésions causées par un transfert d'énergie cinétique et qui présentaient des signes de vie à l'arrivée à un centre de traumatologie de niveau I. Résultats: Ont été comparés 266 patients traités selon le modèle des équipes spécialisées en traumatologie et 111, selon le modèle des urgentologues. Aucun écart n'a été relevé entre les deux systèmes quant au principal critère d'évaluation, soit la proportion de survie au moment du congé ou au bout de 30 jours (0, 88; n=266 contre 0, 89; n=111; p =0, 8608). Conclusions: L'équipe de recherche n'a constaté aucun écart quant à la survie entre le modèle des équipes spécialisées en traumatologie et celui des urgentologues.